Report of the Expert Committee on Small Enterprises - Planning Commission (Planning Commission, 1997)
The Expert Group recommends that the guiding principle of the future course of small scale enterprise (SSE) development policy should be their accelerated growth and competitiveness. Hitherto, the accent of small enterprise development policy was infant industry protection predicated on the assumption that new enterprises cannot withstand predatory competition from large companies. Moreover, government focus has exclusively been on small scale industries. The concept of the small scale sector should now be widened to include small scale business and service enterprises. The principle of protection of fledgling enterprises at the stage of their formation will remain valid in the future as well. Beyond their initial stage of development, incontrovertible evidence exists of the capacity of SSEs to survive competition from large companies in India and elsewhere in the world. SSEs typically survive on the strength of their flexible managements.
Planning Commission Government of India
Planning Commission Government of India